How Terrorism Affects Foreign Direct Investment in Pakistan? - Ali, Hashmat; Qingshi, Wang; Ullah, Irfan; Ali, Zulfiqar (International Journal of Economics and Financial Issues, 2017)
This study is an attempt to investigate the long run interplay between the terrorism and foreign direct investment (FDI) in Pakistan. Terrorism is measured by the number of events, fatalities and injuries with other variables. In this paper, annual time series data is taken from the Global Terrorism Database and World Development indicators, from the period 1980-2015. In the study, we have employed Johansen co-integration approach to examine the long run relationship between the mentioned variables. The study concludes that FDI has a negative significant relationship with fatalities and injuries whereas events have no long-run relationship with FDI. This reflects that fatalities and injuries which occur due to terrorist activities significantly affect the flow of foreign inflows into Pakistan. Keywords: Terrorism, Foreign Direct Investment, Emerging Economy JEL Classifications: F21, E22, C22, G18